Socrative: using mobile devices to promote language learning - Vasconcelos, Sandra
Focusing on the use mobile devices to promote language learning, this chapter documents the use of the student response system Socrative in two German courses taking place at two different Portuguese higher education institutions. It is divided into three different sections. After establishing the project’s theoretical framework, the authors analyse its implementation and present findings, based on users’ perceptions and test results. Aiming at understanding the role mobile devices can play in promoting students’ long-term content retention, this research achieved promising results, not only by confirming students’ expectations towards mlearning, but also by suggesting that mobile initiatives can have a positive effect in motivating students and promoting engagement, change and innovation. Overall, students achieved positive results, with data providing educators with indicators and insights on learner’s learning strategies and progress.